Burden of disease from road traffic and railway noise - a quantification of healthy life years lost in Sweden - Charlotta Eriksson; Theo Bodin; Jenny Selander (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: National quantifications of the health burden related to traffic noise are still rare. In this study, we use disability-adjusted life-years (DALY) measure to assess the burden of disease from road traffic and railway noise in Sweden. METHODS: The number of DALY was assessed for annoyance, sleep disturbance, hypertension, myocardial infarction (MI) and stroke using a method previously implemented by the World Health Organization (WHO). Population exposure to noise was obtained from the Swedish Environmental Protection Agency and the Swedish Transport Administration. Data on disease occurrence were gathered from registers held by the National Board of Health and Welfare and Statistics Sweden. Disability weights (DW) and duration were based on WHO definitions. Finally, we used research-based exposure-response functions or relative risks to estimate disease attributable to noise in each exposure category. RESULTS: The number of DALY attributed to traffic noise in Sweden was estimated to be 41 033 years; 36 711 (90%) related to road traffic and 4322 (10%) related to railway traffic. The most important contributor to the disease burden was sleep disturbances, accounting for 22 218 DALY (54%), followed by annoyance, 12 090 DALY (30%), and cardiovascular diseases, 6725 DALY (16%). CONCLUSIONS: Road traffic and railway noise contribute significantly to the burden of disease in Sweden each year. The total number of DALY should, however, be interpreted with caution due to limitations in data quality.